ChemInform Abstract: Synthesis of Polyhydroxylated Azetidine Iminosugars and 3‐Hydroxy‐N‐methylazetidine‐2‐carboxylic Acid from D‐Glucose. Issue 44 (15th October 2015) - Lawande, Pravin P.; Sontakke, Vyankat A.; Nair, Roopa J.; Khan, Ayesha; Sabharwal, Sushma G.; Shinde, Vaishali S.
Abstract The enantiopure title azetidines are synthesized utilizing an intramolecular Mitsunobu reaction as key step.